The Current Economic Situation in Germany in the Context of Previous Crises - Michael Grömling (Intereconomics, 2025)
This article places the current economic stagnation in Germany in the context of previous crises since 1991. In terms of depth, the current macroeconomic crisis, resulting from the pandemic and geopolitical upheavals, has already exceeded the level of all three previous crises, in some cases considerably. In order to return to the growth path experienced in the last three decades, annual economic growth of 2.5% for the next six years is necessary. There are serious doubts about whether the German economy will return to its previous path of prosperity
Keywords: H11; D70; H50; 330